Muatan Etika dalam Pengajaran Akuntansi Keuangan dan Dampaknya terhadap Persepsi Etika Mahasiswa: Studi Eksperimen Semu - WIWIK UTAMI; TITIK ARYATI; FITRI INDRIAWATI (The Indonesian Journal of Accounting Research, 2013)
This study investigates whether integrating ethical issues in financial accounting course will improve student's ethical perception. The collapse of Enron and the conviction of its accounting firm, Arthur Andersen, has raised a concerns about the role of accounting education in developing etichal and moral behavior among undergraduate accounting students. Students learn ethics and ethical profession usually either from auditing courses or from cases related to auditing. However, ethical issues are not always related to auditing. Ethical problems can occur at any stage during the preparation of financial statements. Using quasi experiment, a posttest-only control group design, we examine wheter loading ethical issues in financial accounting course influence student's ethical perception. In addition, we also test wether interaction between ethical issues in financial accounting course and student GPA (Grade Point Average) influences student's ethics perception. We find that integrating ethical issues in financial accounting course does not affect ethical perception. However, our test show that interaction between loading ethical issues in financial accounting course and student GPA significantly influences the student's. Considering the current climate of good governance, I argue that accounting educators can no longer postpone the integration of ethical issues in accounting curriculum.